Sequential magnetic resonance spectroscopic changes in a patient with nonketotic hyperglycinemia - Ji Hun Shin; So Yoon Ahn; Jeong Hee Shin; Se In Sung; Ji Mi Jung; Jin Kyu Kim; Eun Sun Kim; Hyung Doo Park; Ji Hye Kim; Yun Sil Chang; Won Soon Park (Korean Pediatric Society, 2012)
Nonketotic hyperglycinemia (NKH) is a rare inborn error of amino acid metabolism. A defect in the glycine cleavage enzyme system results in highly elevated concentrations of glycine in the plasma, urine, cerebrospinal fluid, and brain, resulting in glycine-induced encephalopathy and neuropathy. The prevalence of NKH in Korea is very low, and no reports of surviving patients are available, given the scarcity and poor prognosis of this disease. In the current study, we present a patient with NKH diagnosed on the basis of clinical features, biochemical profiles, and genetic analysis. Magnetic resonance spectroscopy (MRS) allowed the measurement of absolute glycine concentrations in different parts of the brain that showed a significantly increased glycine peak, consolidating the diagnosis of NKH. In additional, serial MRS follow-up showed changes in the glycine/creatinine ratios in different parts of the brain. In conclusion, MRS is an effective, noninvasive diagnostic tool for NKH that can be used to distinguish this disease from other glycine metabolism disorders. It may also be useful for monitoring NKH treatment.